The Patient Perspectives on Future Therapeutic Options in NASH and Patient Needs - Cook, Nigel; Geier, Andreas; Schmid, Andreas; Hirschfield, Gideon; Kautz, Achim; Schattenberg, Jörn M.; Balp, Maria-Magdalena (Frontiers in Medicine, 2019)
Background: Non-alcoholic steatohepatitis (NASH) is a chronic liver disease with severe complications and without approved therapies. Currently, there is limited data on the overall burden of the disease for patients or on patient needs and preferences. This study investigates patient preferences in relation to potential future therapies for NASH. In addition, the factors that are relevant to patients and their importance in relation to future treatment options are explored. Method: Telephone in-depth interviews (TDIs) preceded an online 30-minute quantitative survey. The online survey included (1) multiple choice questions (MCQs) on NASH diagnosis and disease background. (2) An exercise to determine patients’ satisfaction levels with information provided at diagnosis, and to explore symptomology in detail. (3) Exercises to evaluate potential new products and product attributes, including a “drag and drop” ranking exercise, and an adaptive choice-based conjoint exercise (ACBC). (4) The EQ-5D-5L questionnaire and the Visual Analogue Scale (VAS), which measures patients’ health status. (5) Collection of socio-demographic data and (6) Questions to measure patient satisfaction with the survey. Results: There were 166 patients included in this study from Canada [n=36], Germany [n=50], the UK [n=30], and USA [n=50]. Fifty seven percent of patients [n = 94] had had a liver biopsy for confirmation of NASH. Patients were often unable to link their symptoms to NASH or other conditions. ACBC results showed that efficacy, defined as “impact on liver status” was the single most important attribute of a potential future NASH therapy. Other attributes considered to have secondary importance included impact on weight, symptom control and the presence of side effects. The EQ-5D utility score was 0.81 and VAS=67.2 Conclusion: “Impact on liver status” is the primary outcome sought. Patients demonstrate a general lack of understanding of their disease and appeared to be unfamiliar with longer-term consequences of NASH. It is necessary to improve patient understanding of NASH and its progressive nature, and there is a need for improving confirmatory diagnosis and monitoring.